Design and Manufacture of A Smart and Portable Multi-Purpose Newborn Incubator (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The incubator device is considered as a closed box that provides the environment required to maintain the condition of the child in the incubators, such as the environment in his mother’s womb, and it depends on providing three basic variables, namely (temperature: it is 37C), (Oxygen O2: where it needs The child needs to double the percentage that the average person needs, which is 20% of the air for normal conditions, while in the incubator needs to provide a ratio of approximately 40%), (Moisture: It is an important factor because if the child inhales dry air with a temperature of 37, it will affect the mucous cells, where a percentage must be provided Humidity appropriate with the proportion of temperature).Also an incubator is described in which an infant can be kept at the proper temperature and humidity, with proper ventilation and, to facilitate respiration, in an atmosphere containing a known and controlled mixture of oxygen and helium. Several Incubator devices are specifically advertised for use with expensive and complicated devices. However, a review of the health problems information, as a review, and the limited literature on performance, to suggest that no device on the market meets evens the most basic requirements of being small, lightweight, rugged, and less cost with an accurate performance.Design and manufacture of portable multi-purpose incubator will serve as monitoring of the newborns conditions and treat Jaundice by phototherapy and solve many problems by being low cost, portable, easy to assemble, lightweight so can be carried around and also easy to use.